Different feeding strategies can affect growth performance and rumen functions in Gangba sheep as revealed by integrated transcriptome and microbiome analyses - Jize, Zhang; Zhuoga, Deqing; Xiaoqing, Zhang; Na, Ta; Jiacuo, Gesang; Cuicheng, Luosang; Bandan, Pingcuo (Frontiers in Microbiology, 2022)
Due to the harsh environment in the Tibetan Plateau, traditional grazing greatly limits the growth potential of local animals and causes severe ecosystem degradation. This is an urgent issue to be solved, which requires alternative strategies for grazing animals in the Tibetan alpine pastoral livestock systems. This study aimed to investigate the effects of different feeding strategies on growth performance and ruminal microbiota-host interactions in the local breed of sheep (Gangba sheep). Thirty 9-month old Gangba sheep (n=10 per group) were assigned to natural grazing (G), semi-grazing with supplementation (T), and barn feeding (F) groups (supplementation of concentrate and oat hay) based on body weight. At the end of the experiment (75 d), all sheep were weighed, rumen fluid was obtained from 6 sheep per group, and ruminal epithelium was obtained from 3 sheep per group. The results showed that: (1) Compared with the G and T groups, the F group significantly increased dry matter intake, average daily gain, and feed conversion ratio of animals. Additionally, Gangba sheep in the F group had higher concentrations of ruminal short-chain volatile fatty acids (VFAs), especially propionate and butyrate (P < 0.05) than sheep in the G and T groups. (2) The principal coordinates analysis indicated a significant difference in bacterial composition among different feed strategies. More specifically, the relative abundance of propionate (unidentified F082 and Succiniclasticum) and butyrate-producing (Eubacterium_coprostanoligenes_group) genera were also observed to be increased in the F group, in which unidentified F082 was identified as a differential biomarker among the three groups according to linear discriminant analysis effect size analysis. (3) The dynamics of the rumen epithelial transcriptome revealed that ECM-receptor interactions, focal adhesion, and PI3K-Akt signalling pathways, which are critical in mediating many aspects of cellular functions such as cell proliferation and motility, were upregulated in the F group. In conclusion, under harsh conditions in the Tibetan alpine meadow, barn feeding increased ruminal VFAs concentrations (especially propionate and butyrate), which stimulated gene expression related to cell proliferation in rumen epithelium, appearing to be superior to natural grazing and semi-grazing in gaining body weight of the local Gangba sheep.